Cost effectiveness of interventions to tackle non-communicable diseases. (2nd March 2012) - Revill, Paul; Sculpher, Mark
Abstract : Estimates of "best buys" in sub-Saharan Africa and South East Asia are a good start, but findings must be assessed within the contexts of particular countries